PENGARUH KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA MAKASSAR - Abdul Haris (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2012)
Productivity plays an important role in the business world, to assess whether employees are productive or not, there should be an assessment where the assessment is intended to detect weaknesses and deficiencies that exist within the company to do repairs later on. Increased productivity is usually associated with the provision of compensation that an important concern for companies, in motivating employees. as a form of reflection of the efforts of organizations to maintain their human resources